A CUG codon adapted two-hybrid system for the pathogenic fungus Candida albicans - Stynen, Bram (Oxford University Press, 2010)
The genetics of the most common human pathogenic fungus Candida albicans has several unique characteristics. Most notably, C. albicans does not follow the universal genetic code, by translating the CUG codon into serine instead of leucine. Consequently, the use of Saccharomyces cerevisiae as a host for yeast two-hybrid experiments with C. albicans proteins is limited due to erroneous translation caused by the aberrant codon usage of C. albicans. To circumvent the need for heterologous expression and codon optimalization of C. albicans genes we constructed a two-hybrid system with C. albicans itself as the host with components that are compatible for use in this organism. The functionality of this two-hybrid system was shown by successful interaction assays with the protein pairs Kis1–Snf4 and Ino4-Ino2. We further confirmed interactions between components of the filamentation/mating MAP kinase pathway, including the unsuspected interaction between the MAP kinases Cek2 and Cek1. We conclude that this system can be used to enhance our knowledge of protein–protein interactions in C. albicans.